PERANAN GURU DALAM PENGELOLAAN KELAS - Nurhalisah Nurhalisah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
Classroom is an important meeting room between students and teachers in teaching process, where teachers transfer their knowledge to students. Flexible class management is important and teachers play an important role in this respect. Skill of class management is important to stimulate student to be productive and dinamic. Moreover, teachers face students who have different cultural background. Diversity does not always means some students are left behind and some are more developed. Instead, diversity is a contributing factor to studens for a change individually.